Diversity and Distribution of Escherichia coli in Three Species of Free-Ranging Australian Pinniped Pups - Fulham, Mariel; Power, Michelle; Gray, Rachael (Frontiers in Marine Science, 2020)
Anthropogenic activities and pollution are impacting marine environments globally. This has resulted in increasing numbers of human-associated phylotypes of Escherichia coli, an indicator of faecal contamination, being found in both aquatic environments and upper trophic marine mammals that are considered sentinels for marine health. The objective of this study was to determine the presence and diversity of E. coli in pups of three species of free-ranging pinnipeds in Australia. Faecal samples (n = 964) were collected between 2016 and 2019 from Australian sea lion (Neophoca cinerea), Australian fur seal (Arctocephalus pusillus doriferus) and long-nosed fur seal (Arctocephalus forsteri) pups from eight breeding colonies extending along the Southern Australian coast. E. coli were isolated from 842 (87.3%) samples and molecular screening was applied to assign isolates to E. coli phylotypes and sub-types. The human associated E. coli phylotype B2 was the most frequently isolated in all species at seven of the eight colonies, with 73.7% of all E. coli isolates belonging to this phylotype. Phylotype distribution did not differ significantly within or across species, breeding colonies or breeding seasons. Further analysis of B2 isolates into sub-types showed a significant difference in sub-type distribution across breeding seasons at two colonies (Seal Rocks and Cape Gantheaume). The predominance of the B2 phylotype could indicate that all colonies are exposed to similar levels of anthropogenic pollution. This widespread occurrence of the human-associated E. coli phylotypes highlights the imperative for ongoing monitoring and surveillance of microbes in both the marine environment and sentinel species.